Comparison of hamstring/quadriceps isokinetic strength ratios and power in tennis, squash and track athletes - Read, M. T.; Bellamy, M. J. (British Journal of Sports Medicine, 1990)
Isokinetic assessment of elite squash, tennis and track athletes confirms the accepted ratio of 60 to 80 per cent hamstring to quadriceps when testing at 90 deg-sec-1 for peak strength (torque). However, significant variations occur at higher test speeds up to 300 deg.sec-1 with the hamstrings becoming more prominent especially (p less than 0.001) in the nonpreferred (NP) leg. There was no significant difference between sports, and wide individual differences occurred. Analysis of (work.sec-1.kg-1 body weight) power showed a significantly higher work output (p less than 0.01) by track athletes than squash and tennis players, but, unlike hamstring/quadriceps ratio, no significant difference between preferred (P) and nonpreferred leg. The maximum power output was achieved around 220 to 250 deg.sec-1. Power between preferred and nonpreferred legs was the same but the torque ratio differed indicating that the hamstrings provided proportionately more work in the NP leg at higher speeds.